FDA Approval Summary: Atezolizumab and Durvalumab in Combination with Platinum‐Based Chemotherapy in Extensive Stage Small Cell Lung Cancer. (25th March 2021) - Mathieu, Luckson; Shah, Sujay; Pai‐Scherf, Lee; Larkins, Erin; Vallejo, Jonathon; Li, Xiaoxue; Rodriguez, Lisa; Mishra‐Kalyani, Pallavi; Goldberg, Kirsten B.; Kluetz, Paul G.; Theoret, Marc R.; Beaver, Julia A.; et al.
Abstract: : The U.S. Food and Drug Administration (FDA) granted approval to atezolizumab and durvalumab in March of 2019 and 2020, respectively, for use in combination with chemotherapy for first‐line treatment of patients with extensive stage small cell lung cancer. These approvals were based on data from two randomized controlled trials, IMpower133 (atezolizumab) and CASPIAN (durvalumab). Both trials demonstrated an improvement in overall survival (OS) with anti–programmed death ligand 1 antibodies when added to platinum‐based chemotherapy as compared with chemotherapy alone. In IMpower133, patients receiving atezolizumab with etoposide and carboplatin demonstrated improved OS (hazard ratio [HR], 0.70; 95% confidence interval [CI], 0.54–0.91; p = .0069), with median OS of 12.3 months compared with 10.3 months in patients receiving etoposide and carboplatin. In CASPIAN, patients receiving durvalumab with etoposide and either cisplatin or carboplatin also demonstrated improved OS (HR, 0.73; 95% CI, 0.59–0.91; p = .0047) with median OS of 13.0 months compared with 10.3 months in patients receiving etoposide and either cisplatin or carboplatin. The safety profiles of both drugs were generally consistent with known toxicities of immune‐checkpoint inhibitor therapies. This review summarizes the FDA perspective and data supporting the approval of these two agents. Implications for Practice: Effective therapeutic options for small cell lung cancer (SCLC) are limited, and there has been modest improvement in the overall survival (OS) of patients with SCLC over the past 3 decades. The approvals of atezolizumab and of durvalumab in combination with chemotherapy for first‐line treatment of patients with extensive stage SCLC represent the first approved therapies with OS benefit for this patient population since the approval of etoposide in combination with other approved chemotherapeutic agents. Additionally, the efficacy results from IMpower133 and CASPIAN lay the groundwork for possible further evaluation in other treatment settings in this disease. Abstract : This review summarizes the FDA perspective and data supporting the approval of atezolizumab and durvalumab for use in combination with chemotherapy for first‐line treatment of patients with extensive stage small cell lung cancer.